Mommy tracks and public policy: on self-fulfilling prophecies and gender gaps in promotion - Lommerud, Kjell Erik (2013)
Consider a model with two types of jobs. The profitability of promoting a worker to a fast-track job depends not only on his or her observable talent, but also on incontractible effort. We investigate whether self-fulfilling expectations may lead to higher promotion standards for women. If employers expect women to do more household work than men, thereby exerting less effort in their paid job, then women must be more talented to make promotion profitable. Moreover, specialization in the family will then result in women doing most of the household work. Such self-fulfilling prophecies can be defeated: both affirmative action and family policy can make women spend more effort in the market, which can lead the economy to a non-discriminatory equilibrium. However, we find that it is unlikely that temporary policy can move the economy to a symmetric equilibrium: policy must be made permanent. Anti-discrimination policy need not enhance efficiency, and from a distribution viewpoint this is a policy with both winners and losers.